Voltage oriented control of three‐phase boost PWM converters - Lechat, Sylvain Sanjuan (My University, 2010)
In a plug‐in hybrid electric vehicle, the utility grid will charge the vehicle battery through the battery charger. For a three‐phase grid supply voltage, three‐phase boost rectifiers are a commonly used scheme for chargers. Bi‐directional power transfer capability and unit power factor operation are interesting features that can be achieved by the method proposed in this thesis. Different control strategies have been proposed to control the converter. The Voltage Oriented Control is one of these methods based on high performance dq‐coordinate controllers. The Voltage Oriented Control method for a three‐phase boost rectifier have been designed and simulated. Moreover, an implementation of the system has been started. The system simulation has been done using Matlab/Simulink software. Feedforward decoupled current controller has been designed along with Pulse Width Modulation scheme to control the battery charging. The controller, that is, a current controller and a DC‐link voltage controller, have been designed using a method called Internal Model Control. The simulation results have been presented and the control system performance evaluated in response to the load and dc‐bus voltage step changes. dSpace system have been used for practical implementation. The system is directly running a Simulink model as a controller. The Simulink files have been developed for this purpose. A brief explanation of the system configuration has been provided for the experimental system.
Keywords: Elkraftteknik; Electric power engineering